A Therapeutic Role for Survivin in Mitigating the Harmful Effects of Ionizing Radiation. (17th April 2016) - Carruthers, Katherine H.; Metzger, Gregory; Choi, Eugene; During, Matthew J.; Kocak, Ergun
Abstract : Background . Radiation therapy is a form of adjuvant care used in many oncological treatment protocols. However, nonmalignant neighboring tissues are harmed as a result of this treatment. Therefore, the goal of this study was to induce the production of survivin, an antiapoptotic protein, to determine if this protein could provide protection to noncancerous cells during radiation exposure. Methods . Using a murine model, a recombinant adenoassociated virus (rAAV) was used to deliver survivin to the treatment group and yellow fluorescence protein (YFP) to the control group. Both groups received targeted radiation. Visual inspection, gait analysis, and tissue histology were used to determine the extent of damage caused by the radiation. Results . The YFP group demonstrated ulceration of the irradiated area while the survivin treated mice exhibited only hair loss. Histology showed that the YFP treated mice experienced dermal thickening, as well as an increase in collagen that was not present in the survivin treated mice. Gait analysis demonstrated a difference between the two groups, with the YFP mice averaging a lower speed. Conclusions . The use of gene-modification to induce survivin expression in normal tissues allows for the protection of nontarget areas from the negative side effects normally associated with ionizing radiation.